Respostas
respondido por:
5
Basta usar a seguinte fórmula,
1,8 * (T - 273) = °F - 32
1,8 * (293 - 273) = °F - 32
1,8 * 20 = °F - 32
36 = °F - 32
°F = 32 + 36
°F = 68
1,8 * (T - 273) = °F - 32
1,8 * (293 - 273) = °F - 32
1,8 * 20 = °F - 32
36 = °F - 32
°F = 32 + 36
°F = 68
respondido por:
8
utilize a fórmula:
°F= 1,8.(K-273)+32
°F=1,8.(20)+32
°F=36+32
°F=68
°F= 1,8.(K-273)+32
°F=1,8.(20)+32
°F=36+32
°F=68
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás